Maize feeds and influence of xylanase on broiler digestion of starch - Lee, S.A. (2016)
The primary cereal grain used in poultry feed worldwide is maize. An understanding of how and where broiler chickens digest native starches, this being the major energy component of maize, and the influence that exogenous xylanase has on this process, is essential when optimising nutrient utilisation of a diet. In this project, both in vitro and in vivo models were used to understand broiler digestion of starches in different maize-based diets: native maize starch, maize grit and maize-soy with or without xylanase (Econase XT 25 at 100 g/t; 18,100 BXU/kg). An in vitro model to simulate the digestive tract of broilers using a ball milling technique to mimic the chicken gizzard was designed to investigate differences in the digestion of starches between the various diets. Reduced starch crystallinity and particle size of the diet was shown when samples were ball milled in HCl-pepsin, compared to roller mixed samples, leading to a greater glucose release when these samples were incubated with pancreatin. The maize-soy diet gave the greatest glucose release with pancreatin, with native maize starch giving the lowest, indicating that the processing of diets prior to digestion as well as the surrounding food matrix can impact on the digestion of starches in feed. In all in vivo trials, starch fraction measurements and SEM imaging of digesta collected from the gizzard, upper and lower small intestine, revealed the progression of starch granule digestion through the tract. Despite birds being starved prior to feeding, broilers ingested little of the native maize starch diet. Nonetheless, predominantly intact granules were evident in the gizzard, with signs of amylase attack becoming apparent in the small intestine. Following starvation, starch granules were still observed throughout the tract of birds, suggesting the presence of resistant starches. Higher digesta pH values were observed when birds were fed a maize-soy diet which gave pH 3.56, 6.70, 7.70 for the gizzard, and upper and lower small intestine, respectively, compared to pH 2.47, 6.49, 7.34 for the maize grit diet, an effect that could potentially impact on digestive processes. In feeding trials with broilers, inclusion of xylanase into the maize-soy diet and feeding on a single occasion revealed no apparent difference in the matrices surrounding the starch granules in digesta. This suggested that xylanase may be working indirectly in vivo through some physiological change in the digestion mechanism rather than direct action on the feed. To test this hypothesis, birds were fed xylanase for different lengths of time before slaughter. Peptide YY concentration in the blood was higher during the first few weeks of supplementation, with longer periods of supplementation nulling this effect, suggesting that xylanase may be acting through a prebiotic mechanism. RT-qPCR results revealed a trend towards an increase in glucose transporter (GLUT2 and SGLT1) expression at 2 and 3 weeks of xylanase supplementation, respectively. This also correlated to an increase in glucose concentration in the blood from 3 weeks of xylanase inclusion, suggesting a greater absorption capacity of birds. These results may indicate a potential mechanism of xylanase action in maize-based diets, although further work is required to confirm these findings.